High Maternal Neonatal Mortality and Morbidity in Pregnancy with Eisenmenger Syndrome - Erry Gumilar Dachlan; Amirah; Nareswari Cininta; Rizky Pranadyan; Alisia Yuana Putri; Yudi Her Oktaviono; Muhammad Ilham Aldika Akbar (Hindawi Limited, 2021)
Objectives. This study is aimed at evaluating the maternal and perinatal characteristics and pregnancy outcomes of ES. Material and Methods. This is a retrospective cohort study of pregnancy with Eisenmenger syndrome (ES) in Dr. Soetomo Hospital from January 2018 to December 2019. Total sampling size was obtained. We collected all baseline maternal-perinatal characteristic data, cardiac status, and pregnancy outcomes as primary outcomes. The maternal death cases were also evaluated, and we compared characteristics based on defect size (< or >3 cm). Results. During study periods, we collected 18 cases with ES from a total of 152 pregnancies with heart disease. The underlying heart disease type includes atrial septal defect (ASD), ventricle septal defect (VSD), and patent ductus arteriosus (PDA). All cases suffered pulmonary hypertension (PH), 3 cases moderate, and 15 cases as severe. 94% of cases fall into heart failure (DC FC NYHA III-IV) during treatment. The majority of cases are delivered by cesarean section (88.9%). Pregnancy complications found include preterm birth (78%), low birthweight (94%), intrauterine growth restriction (55%), oligohydramnios (16%), severe preeclampsia (33%), and placenta previa (5.5%). Large defect group has an older maternal ages (30.18±4.60 vs. 24.15±2.75; p=0.002), higher clinical sign (100 vs. 40%, p=0.003), and higher preterm delivery rate (100% vs. 69%, p=0.047) compared to small defect groups. The R to L or bidirectional shunt is significantly higher at the large defect group (13 vs. 5 cases, p=0.006, 95% confidence interval: -1.156 to -0.228). There were seven maternal death cases caused by shock cardiogenic. Conclusions. Pregnancy with ES is still associated with very high maternal neonatal mortality and morbidity. The larger defect size is correlated with clinical performances and pregnancy outcomes. Effective preconception counseling is the best strategy to reduce the risk of maternal and neonatal death in ES women.